Catherine Barkley As a Norm Woman: a Feminist Perspective of Hemingway’S a Farewell to Arms: Exploring the Evolution of the Ideal Woman in Hemingway's A Farewell to Arms (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Measured by the gender standards prevailing during the1920s, when Hemingway wrote A Farewell to Arms, Catherine emerged as a modern,independent young woman–quite possibly representing Hemingway’s ideal woman.She is an improved, more modern version of Norm Woman. True to the ideals ofthe Norm Woman that emerged during Hemingway’s time, Catherine is a good sportand pal, possessing traditional maternal and domestic qualities without thatcruelty or mannishness displayed by some strong women in Hemingway’s laterfiction. These ideal women are ready and qualified to run away with the manthey love and to help him domesticate the world of his wishful dreams. Contraryto Leslie Fiedler’s assertion that “Hemingway’s men prefer each other’s companyand the dangers of the manly world to the responsibilities associated withwomen and civilization” (355), the protagonist of this novel flees from thecorrupt and untrustworthy male world into a woman’s arms.